Hemodynamic causes of spontaneous isolated superior mesenteric artery dissection - Keli Yin, BE; Li Hou, BE; Chengxin Weng, PhD; Jianjin Yue, BE; Tinghui Zheng, PhD; Ding Yuan, PhD (JVS-Vascular Insights)
Background: Recently, spontaneous isolated superior mesenteric artery dissection (SISMAD) has been widely reported, and the hemodynamic causes of SISMAD have been assumed to be the same as those of aortic dissection. However, the hemodynamic causes of SISMAD are still unknown, and the relationship between two dissections is not clear. Methods: The predissected and healthy superior mesenteric artery models were reconstructed based on computed tomography angiography of 10 patients with SISMAD and 10 healthy subjects, respectively. Then the computational fluid dynamics method was used to find the hemodynamic difference between the two groups. Results: First, the blood flow of the patients was helical at the entrance, whereas the blood flow of the healthy people was laminar; secondly, the oscillatory shear indices of the pre-SISMAD patients were significantly higher than those in healthy subjects (P < .05). Meanwhile, the SISMAD initial tear location corresponded to the high oscillatory shear index zone. Average time-averaged wall shear stress was not significantly different between the two groups (P = .42). The deviation angles of the superior mesenteric artery from the abdominal aorta in pre-SISMAD models were significantly smaller than those in healthy subjects (44.03° ± 10.25° vs 64.23° ± 9.34°, P < .01). Conclusions: Unlike the occurrence of aortic dissection, SISMAD may be due to the continuous back and forth changes of blood flow along the mainstream direction during a cardiac cycle caused by the appearance of helical flow at superior mesenteric artery entrance.